2012
DOI: 10.1590/s0103-64402012000200002
|View full text |Cite
|
Sign up to set email alerts
|

1-Year clinical study of indirect resin composite restorations luted with a self-adhesive resin cement: effect of enamel etching

Abstract: In vitro studies have recommended enamel-etching before luting indirect restorations with self-adhesive resin cement. However, there is no scientific proof that this procedure has any clinical relevance. Thus, the aim of this study was to evaluate the effect of enamel-etching on the marginal quality of indirect composite resin restorations (inlay/onlay) using the self-adhesive cement RelyX Unicem clicker. Forty-two posterior teeth were selected from 25 patients that presented one or two teeth with large restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
2
9
0
4
Order By: Relevance
“…Furthermore, marginal discoloration was also found to be higher in the nonetch group, probably because the fillers were cropped out from the resin matrix during tooth brushing . Azevedo et al also stated that enamel etching had no clinical relevance on the marginal quality of indirect composite resin restorations. Overall, the advantage of selective enamel etching upon marginal adaption in the clinical situation could not be confirmed by either of these two studies, although it was advocated for in vitro studies; however, it should be mentioned that, in these two studies, RelyX was bonded to enamel surfaces only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, marginal discoloration was also found to be higher in the nonetch group, probably because the fillers were cropped out from the resin matrix during tooth brushing . Azevedo et al also stated that enamel etching had no clinical relevance on the marginal quality of indirect composite resin restorations. Overall, the advantage of selective enamel etching upon marginal adaption in the clinical situation could not be confirmed by either of these two studies, although it was advocated for in vitro studies; however, it should be mentioned that, in these two studies, RelyX was bonded to enamel surfaces only.…”
Section: Resultsmentioning
confidence: 99%
“…Six of the 14 in vivo studies found dealt with this issue . All authors agreed that self‐adhesive resin cements showed less postoperative sensitivity than the classic total‐etch technique or conventional cements, such as glass ionomer or zinc phosphate cements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bonding mechanism of this cement is not yet completely understood, but differs from that obtained with self-etched adhesives as no distinct demineralization and hybridization was observed during TEM morphological interface examination [24,25] . Many laboratory and clinical studies [26][27][28] noticed an inefficient bonding effectiveness for this particular adhesive. It is well reported that acid etching provides the most reliable bond strength to enamel [32] .…”
Section: Resultsmentioning
confidence: 99%
“…Since the introduction of bonding systems and composite resins, wear and microleakage were the primary clinical limitations, mainly in posterior restorations (1)(2)(3)(4)(5)(6)(7)(8). The relative porosity of the restorative and absorption/adsorption of oral fluids may also allow staining agents to penetrate the material (9).…”
Section: Introductionmentioning
confidence: 99%